Answer :

To prove: (sin 3x + sin x)sin x + (cos 3x – cos x)cos x= 0


Proof:


Take LHS:


(sin 3x + sin x)sin x + (cos 3x – cos x)cos x


= (sin 3x)(sin x) + sin2 x + (cos 3x)(cos x) – cos2 x


= [(sin 3x)(sin x) + (cos 3x)(cos x)] + (sin2 x – cos2 x)


= [(sin 3x)(sin x) + (cos 3x)(cos x)] – (cos2 x – sin2 x)


= cos(3x – x) – cos 2x


{ cos 2x = cos2 x – sin2 x &


cos A cos B + sin A sin B = cos(A – B)}


= cos 2x – cos 2x


= 0


= RHS


Hence Proved


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

0 ≤ x ≤ π aRD Sharma - Mathematics

Prove that:RD Sharma - Mathematics